2003
DOI: 10.1074/jbc.m207518200
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 2 Interacts with Cyclin-dependent Kinase 11 (CDK11) in Vivo and Phosphorylates Both the RNA Polymerase II Carboxyl-terminal Domain and CDK11 in Vitro

Abstract: The PITSLRE protein kinases, hereafter referred to as cyclin-dependent kinase 11 (CDK11) due to their association with cyclin L, are part of large molecular weight protein complexes that contain RNA polymerase II (RNAP II) as well as numerous transcription and RNA processing factors. Data presented here demonstrate that the influence of CDK11 p110 on transcription and splicing does not involve phosphorylation of the RNAP II carboxyl-terminal domain by CDK11 p110 . We have isolated a DRB-and heparin-sensitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 30 publications
(13 reference statements)
6
76
0
Order By: Relevance
“…1C). This result is consistent with previous analyses of CDK11 p110 functional domains, which indicate that this same region of the amino-terminal domain is necessary for the majority of the protein-protein interactions between this protein kinase and other proteins (16,17,21), whereas the carboxylterminal half of the protein encodes the catalytic domain of the protein kinase that is most homologous to CDK2 (18).…”
Section: Cdk11 Interacts With and Phosphorylates Splicing Factor 9g8supporting
confidence: 82%
See 2 more Smart Citations
“…1C). This result is consistent with previous analyses of CDK11 p110 functional domains, which indicate that this same region of the amino-terminal domain is necessary for the majority of the protein-protein interactions between this protein kinase and other proteins (16,17,21), whereas the carboxylterminal half of the protein encodes the catalytic domain of the protein kinase that is most homologous to CDK2 (18).…”
Section: Cdk11 Interacts With and Phosphorylates Splicing Factor 9g8supporting
confidence: 82%
“…The inclusion of the kinase-inactive form of the CDK11 p110 protein kinase in the in vitro kinase assay was essential for this experiment, since we have previously shown that the casein kinase 2 protein kinase interacts and co-purifies with CDK11 p110 (21). The inclusion of a kinaseinactive form of CDK11 p110 also eliminates the possibility that another co-purifying or contaminating protein kinase is responsible for the in vitro phosphorylation of the 9G8 substrate.…”
Section: Cdk11 Interacts With and Phosphorylates Splicing Factor 9g8mentioning
confidence: 99%
See 1 more Smart Citation
“…54 Thus, this class of cyclin/CDK pairs appears to be regulated by complex formation-induced stabilization of subunits. In contrast to most of the CDKs, which require phosphorylation of a conserved threonine in the T-loop, 42,50,55 CDK8 is proposed to be solely activated by interaction with its cyclin. 39 Additional mechanisms of regulation of this subclass of CDKs include autophosphorylation (CDK9, 11) 41 and activation-dependent dimerization (CDK11).…”
Section: Conventional Cyclin-cdk Interactionsmentioning
confidence: 99%
“…2,49 Cyclin-CDK pairs involved in transcriptional control and mRNA splicing, e.g., cyclin C/CDK8 and cyclin L/CDK11, appear to be mainly regulated by their assembly into large multi-protein complexes. [50][51][52] Via their C-terminal cyclin fold, "transcriptional" cyclins make additional interactions with the catalytic subunit, resulting in a more open conformation suitable to accommodate additional proteins. 41,42 The formation of these complexes usually stabilizes one of the partners, like the CDK subunit in the cyclin T1/CDK9 53 or the cyclin subunit in the cyclin C/CDK8 complex.…”
Section: Conventional Cyclin-cdk Interactionsmentioning
confidence: 99%